A conceptual design of spatial calibration for optical see-through head mounted display using electroencephalographic signal processing on eye tracking - Tomi, A. (Springer Verlag, 2017)
One of vital issue in Optical See-Through Head Mounted Display (OST HMD) used in Augmented Reality (AR) systems is frequent (re)calibrations. OST HMD calibration that involved user interaction is time consuming. It will distract users from their application, which will reduce AR experience. Additionally, (re)calibration procedure will be prone to user errors. Nowadays, there are several approaches toward interaction-free calibration on OST HMD. In this proposed work, we propose a novel approach that uses EEG signal processing on eye movement into OST HMD calibration. By simultaneously recording eye movements through EEG during a guided eye movement paradigm, a few properties of eye movement artifacts can be useful for eye localization algorithm which can be used in interaction-free calibration for OST HMD. The proposed work is expected to enhance OST HMD calibration focusing on spatial calibration formulation in term reducing 2D projection error. © Springer International Publishing AG 2017.